Analisis Profitabilitas dan Struktur Modal terhadap PPh Badan Terhutang pada Perusahaan Manufaktur Industri Pupuk Organik - Titalia Septiana Efendy; Fauziyah Fauziyah; Sri Kalimah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine and analyze the effect of profitability and capital structure on corporate income tax (PPh) payable at PT Kediri Tani Sejahtera during 2018–2022. The research uses a quantitative descriptive approach with primary data obtained through interviews and documentation of the company’s financial statements, including annual income statements and balance sheets. The analysis involves calculating profitability ratios, namely Return on Assets (ROA) and Return on Equity (ROE), as well as capital structure ratios, namely Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), and comparing them with the annual corporate income tax payable. The results indicate that net profit before tax and PPh payable were below 4.8 billion IDR annually. Trend Moment analysis shows that profitability has a significant relationship with PPh payable, while capital structure also affects PPh, though not directly. The company’s asset size impacts depreciation recognized as an expense in the income statement, influencing the tax amount due. This study confirms that managing profitability and capital structure is crucial for tax planning and compliance in manufacturing companies, particularly in the organic fertilizer industry.